1998
DOI: 10.1111/j.1365-2621.1998.tb17920.x
|View full text |Cite
|
Sign up to set email alerts
|

Model for Combined Effects of Temperature, pH and Water Activity on Thermal Inactivation of Bacillus cereus Spores

Abstract: Initially, the effect of water activity (a w ) on heat resistance of Bacillus cereus spores (decimal reduction time) was investigated. A linear relationship was found between log D and 1-a w . The combined effects of temperature (85-105°C), pH (4.5-6.5) and water activity (0.80-1) were then studied. A four parameter model was fitted to the data. This model appeared to be parsimonious with each parameter having a biological significance. Interactions between factors were observed but they accounted for <2.4% of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(63 citation statements)
references
References 27 publications
(18 reference statements)
5
53
0
3
Order By: Relevance
“…It is, however, suggested that the highest risk for consumers is foodstuffs with long expiration periods, such as cured meats for grilling, spreads and specialities, etc. Formerly published data (Gaillard et al 1998) confirm our thesis that pH and cold temperature cannot be considered as quite secure factors for the restriction of the growth and activity of B. cereus. The isolates from ready-to-cook products and from swabs were characterised by lower quantities of enterotoxin production in comparison with the group of isolates coming from meat products.…”
Section: Resistance To Selected Antimicrobial Substancessupporting
confidence: 65%
“…It is, however, suggested that the highest risk for consumers is foodstuffs with long expiration periods, such as cured meats for grilling, spreads and specialities, etc. Formerly published data (Gaillard et al 1998) confirm our thesis that pH and cold temperature cannot be considered as quite secure factors for the restriction of the growth and activity of B. cereus. The isolates from ready-to-cook products and from swabs were characterised by lower quantities of enterotoxin production in comparison with the group of isolates coming from meat products.…”
Section: Resistance To Selected Antimicrobial Substancessupporting
confidence: 65%
“…Although pasteurization is known to inactivate the vegetative cells, spores of B. cereus are known to be highly heat resistant and are usually unaffected by physical, chemical and biological factors (Gaillard et al 1998;González et al 1999). In general, investigations have addressed these aspects relating to either vegetative cells or spores and not both the phases together of one and the same species, except for a not very recent study (Byrne et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The characteristically high heat resistance of dormant bacterial spores is explained by the low water concentration in the core Abbreviations : CPMAS, cross-polarization magic angle spinning ; DPA, dipicolinic acid ; SPMAS, single-pulse magic angle spinning ; STEM, scanning transmission electron microscopy ; TEM, transmission electron microscropy. (Nakashio & Gerhardt, 1985 ;Beaman & Gerhardt, 1986 ;Setlow, 1994 ;Gaillard et al, 1998). Water contents of spore protoplasts were found to vary among Bacillus species between 26 and 55 % (Nakashio & Gerhardt, 1985 ;Lindsay et al, 1985 ;Beaman et al, 1984 ;Beaman & Gerhardt, 1986).…”
Section: Introductionmentioning
confidence: 99%